Estudo dos perfis pela teoria dinâmica da difração de Raios – X - Muniz, Francisco Tiago Leitão (2012)
The dynamical theory of X-ray diffraction is a theory wich, unlike the kinematic theory, has its origin in Maxwell's equations and in the Bragg’s Law with a more complete and appropriate physical treatment that takes into account all interactions between the electromagnetic wave fields within the crystal and also takes into account the physical properties of the crystal. These interactions bring bout effects that are neglected in the kinematic theory, a most traditional and most commonly used theory when it comes to thin crystals diffraction. This study aims to calculate the diffraction profile by using the dynamic theory in order to confirm and evaluate the presence of the dynamic effects which in turn are intensified by increasing the thickness of the sample. These effects are: the anomalous absorption and the effects of extinction. Data were computed and plotted using the programming language Fortran 90 applied on single crystals of silicon, germanium, gallium arsenide and indium phosphide, with the aim of studying the influence of the thickness of the crystal and the ratio of imaginary and real parts of the structure factor, the diffraction pattern. Finally, with the width at half height, determined by the profiles graphics, in function of the thickness it could be concluded that the Scherrer equation fits well when applied to relatively thin crystals, a region where the dynamic effects are negligible.